Model Caribbean workplace policy on HIV/AIDS 2007 (CARICOM/PANCAP GeorgetownGY, 2007)
Presents model policy based on the ILO code of practice on HIV and the World of Work, and takes into account national level policies in several regional countries. Draws from enterprise level policies from some national and regional institutions and regional and multi-national enterprises.
Developed in response to recommendations of the Tenth Special Meeting of the COHSOD, held in Trinidad and Tobago on 9-10 June 2006.